Measurement of the inclusive t t ¯ cross section in pp collisions at √s=5.02 TeV using final states with at least one charged lepton - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Springer Nature, 2018)
The top quark pair production cross section (σt t ¯) is measured for the first time in pp collisions at a center-of-mass energy of 5.02 TeV. The data were collected by the CMS experiment at the LHC and correspond to an integrated luminosity of 27.4 pb−1. The measurement is performed by analyzing events with at least one charged lepton. The measured cross section is σt t ¯ = 69.5 ± 6.1 (stat) ± 5.6 (syst) ± 1.6 (lumi) pb, with a total relative uncertainty of 12%. The result is in agreement with the expectation from the standard model. The impact of the presented measurement on the determination of the gluon distribution function is investigated.